(untitled) (International Journal of Banking and Finance, 2011)
This research attempts to model performance measurement for the firms listed on Indonesia Stock Exchange (IDX) using the stochastic frontier approach. There are 121 firms analyzed over the period of 2000-05 with 726 pooled observations. We also test whether firm’s age, size, market share, manufacturing classifications and time period have effects on the technical inefficiency of the manufacturing sector. Our findings reveal that the average technical efficiency of the tested firms is 0.7149, which is below the efficiency frontier: factors that affect inefficiency are found and explained. Our research has offered notable original contributions to performance measurement and provides insights or managerial decision making on operational performance of listed firms in an increasingly competitive Indonesian economy.